Design considerations to prevent thermal hazards in cylindrical lithium-ion batteries: An analytical study. (June 2021) - Moosavi, Amin; Ljung, Anna-Lena; Lundström, T. Staffan
Abstract: Lithium-ion batteries have a high energy content, which makes them a great option for mobile storage applications. However, there are some serious concerns regarding their performance in terms of uncontrolled overheating. In this study, an analytical thermal model is developed based on the integral transform technique to predict the temperature field in a cylindrical lithium-ion cell. The temperature rise and the thermal gradient, as the significant parameters for the safety and performance assessment of lithium-ion batteries, are investigated for the lithium-ion cell. Moreover, the thermal behavior of the lithium-ion cell is comprehensively studied for different thicknesses of the component layers. It is found that the optimum thickness of the positive active material, the negative active material, the positive current collector, and the negative current collector for the efficient thermal operation of the lithium-ion cell is 180, 34, 21, and 20 μ m, respectively. Furthermore, the performance of the optimized jelly-roll is assessed for the different types of cylindrical lithium-ion cells. The results indicate that the 21700 cell has the best thermal performance for use in high charge/discharge applications. Highlights: An analytical thermal model is presented for a cylindrical lithium-ion battery. The model is validated against experimental data sets from the literature. A novel parameter for the thermal assessment of lithium-ion batteries is proposed. The results yield the optimum thickness of the layers within the battery cell. The thermal performance of different types of cylindrical batteries is compared.